A multi-level, multi-jurisdictional strategy: Transnational tobacco companies' attempts to obstruct tobacco packaging restrictions. Issue 4 (3rd April 2019) - Hawkins, Benjamin; Holden, Chris; Mackinder, Sophie
ABSTRACT: Despite the extensive literature on the tobacco industry, there has been little attempt to study how transnational tobacco companies (TTCs) coordinate their political activities globally, or to theorise TTC strategies within the context of global governance structures and policy processes. This article draws on three concepts from political science – policy transfer, multi-level governance and venue shifting – to analyse TTCs' integrated, global strategies to oppose augmented packaging requirements across multiple jurisdictions. Following Uruguay's introduction of extended labelling requirements, Australia became the first country in the world to require tobacco products to be sold in standardised ('plain') packaging in 2012. Governments in the European Union, including in the United Kingdom and Ireland, adopted similar laws, with other member states due to follow. TTCs vehemently opposed these measures and developed coordinated, global strategies to oppose their implementation, exploiting the complexity of contemporary global governance arrangements. These included a series of legal challenges in various jurisdictions, alongside political lobbying and public relations campaigns. This article draws on analysis of public documents and 32 semi-structured interviews with key policy actors. It finds that TTCs developed coordinated and highly integrated strategies to oppose packaging restrictions across multiple jurisdictions and levels of governance.